Nowe prawa człowieka a godność osoby (Wy− kład zaprezentowany 18 maja 2011 roku na Katolickim Uniwersytecie Lubelskim Jana Pawła II) - MIGLIORE, Celestino (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The paper analyzes new human rights, especially reproductive and sexual ones, in the light of the relevant pronouncements of John Paul II and Benedict XVI. The author claims that although in the changing historical and social conditions the list of human rights cannot be considered as definite, the proposal of every new right should be accompanied by reflexion on the concept of the human per− son presupposed by the right in question. New rights that disregard the social nature of man and promote individualism consitute a threat to the unity of the human person and to the stability of community bonds. Summarized by Patrycja Mikulska